Hypernatremic Dehydration in Breast Fed Infants: Lessons from a Baby-Friendly Hospital. (3rd December 2020) - Butler, B; Trotman, H
Abstract: Aim: To determine the incidence, presentation and outcome of all neonates admitted to the University Hospital of the West Indies with a diagnosis of breastfeeding associated hypernatremic dehydration during a 15-year period and make comparisons with an earlier study done at the institution. Methods: A retrospective review of the files of neonates admitted to the neonatal unit with breastfeeding associated hypernatremic dehydration between January 2002 and December 2016 was conducted. Data on maternal and neonatal demographics, presentation, laboratory results and outcome were extracted and descriptive analyses performed. Statistical significance was taken at the level p  < 0.05. Results: Eighty neonates were entered into the study, 79 were inborn giving an incidence of 2.5 per 1000 live births. Fifty-five (71%) mothers were primiparous, with a mean ± SD age of 29.5 ± 5.6 years and mean ± SD length of hospital stay 2.6 ± 1.5 days. Fifty-six (71%) neonates were exclusively breastfed with a mean ± SD age at presentation of 5.6 ± 3.8 days, mean ± SD percentage weight loss of 16.3% ± 6.1% and a mean serum ± SD sodium of 156.1 ± 8.3 mmol/l. Fifty-four (68%) neonates were admitted from home and 22 (28%) from the postnatal ward. Complications seen included acute kidney injury 6 (8%), seizures 2 (3%), hypotonia 1 (1%) and bradycardia 1 (1%). The neonates were detected earlier, presented with a significantly lower mean serum sodium, urea and creatinine ( p  < 0.05), had less severe complications and no deaths compared with neonates in the previous study. Conclusion: Early intervention can make a positive impact on the severity and complications of breastfeeding associated hypernatremia.